Analysis of Artificial Intelligence Usage and Its Implications for the Academic Ethics of PAI Class of 2022 Students in Scientific Writing - Meylila Putri Mauliyanti; Muliatul Maghfirah (Journal of Educational Sciences, 2026)
The rapid advancement of information technology, particularly Artificial Intelligence (AI), has significantly influenced academic practices in higher education. However, studies specifically examining AI use and its academic ethics implications within Islamic Religious Education (PAI) students at Islamic higher education institutions remain limited. This study aims to analyze and describe two aspects: the forms of AI use by Islamic Religious Education (PAI) 2022 students at UIN Madura in academic writing, and the implication of AI use on their academic ethics. This research employed a qualitative descriptive approach, with data collected through structured and semi-structured interviews, participatory observation, and documentation. Data analysis was conducted through four stages. The findings reveal three forms of AI use: concept and framework generation, paraphrasing and grammar improvement, reference and citation searching. Regarding the implication on academic ethics, the dominant negative implication include a significant decline in originality, unverified references and citations, and reduced critical thinking ability and academic independence. Positive implication include time efficiency and improved digital literacy. A notable finding is that students are aware of plagiarism risks yet continue using AI excessively due to the absence of clear institutional regulations. Future research should focus on developing AI literacy programs and ethical policy frameworks for Islamic higher education institutions.